Women’s City: New Features of Lithuanian Literature’s Vilnius Text - Vidugirytė, Inga (Literatūra, 2025)
In the article, I return to the Vilnius Text (VT) concept, characteristic of Pavel Lavrinec’s and Tomas Venclova’s work. I discuss the new features of VT against the backdrop of the Lithuanian canon of VT – the literary works of Ričardas Gavelis, Jurgis Kunčinas, and Antanas Ramonas created in the late 20th century. I suggest that these works were a response to a significant historical event of the city in the middle of the 20th century, specifically, the recovery of Vilnius as the capital of Lithuania. I raise the question of the response of Lithuanian literature to the most important event in recent history – the regaining of the Independence of Lithuania. I believe it was the city created by women authors in the 21st century. The women’s city is lined with the idea of Independence itself – free from the dominant historical narratives, the masculine gaze, and stereotypes. The article also shows that the concept of the city text, if accurately used, is still fruitful in analyzing city literature. It enables the connection between the city’s historical events and the development of literature and comparative research in the different national traditions of VT.
Keywords: Vilnius text; contemporary Lithuanian literature; women’s literature; Vilnius literature; literary maps